2011
DOI: 10.1037/a0021861
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of age-related decline in interpretation of emotion cues from prosody.

Abstract: Older adults are not as good as younger adults at decoding prosodic emotions. We sought to determine the specificity of this finding. Performance of older and younger adults was compared on a prosodic emotion task, a "pure" prosodic emotion task, a linguistic prosody task, and a "pure" linguistic prosody task. Older adults were less accurate at interpreting prosodic emotion cues and nonemotional contours, concurrent semantic processing worsened interpretation, and performance was further degraded when identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 56 publications
3
31
2
1
Order By: Relevance
“…Concerning our main aim, age-related prosodic emotion interpretation differences (Dupuis & Pichora-Fuller, 2010;Mitchell, 2007;Mitchell, et al, 2011) do indeed extend towards discrimination judgements. We can reject the hypothesis that age-related differences in prosodic emotion recognition are an artefact of additional unrelated cognitions, because in a discrimination task devoid of labelling cognitions, age-related decline in emotion perception was still observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning our main aim, age-related prosodic emotion interpretation differences (Dupuis & Pichora-Fuller, 2010;Mitchell, 2007;Mitchell, et al, 2011) do indeed extend towards discrimination judgements. We can reject the hypothesis that age-related differences in prosodic emotion recognition are an artefact of additional unrelated cognitions, because in a discrimination task devoid of labelling cognitions, age-related decline in emotion perception was still observed.…”
Section: Discussionmentioning
confidence: 99%
“…Lead-in and -out silence were manually trimmed. The processing and acoustic characteristics of stimuli are described in more detail in Mitchell et al (Mitchell, Kingston, & Barbosa Boucas, 2011).…”
Section: Experimental Tasksmentioning
confidence: 99%
“…Because of progressive reductions in perceived time horizons, aging would lead to increased prioritization of goals related to emotional well-being, resulting in increased efforts to allocate cognitive resources towards positive information and away from negative onepositivity effect (Carstensen & Mikels, 2005;Charles & Carstensen, 2007Mather & Carstensen, 2005;Reed & Carstensen, 2012;Samanez-Larkin & Carstensen, 2011). Findings that age effects are smaller for the recognition of happiness as compared to negative emotions are often interpreted within this framework (Laukka & Juslin, 2007;Mill et al, 2009;Mitchell et al, 2011;Riediger, Voelkle, Ebner, & Lindenberger, 2011;Williams et al, 2006). However, the interaction between valence and age is not consistently obtained (e.g., Isaacowitz et al, 2007;Lambrecht et al, 2012;Ruffman et al, 2008).…”
Section: Aging and Emotion Recognitionmentioning
confidence: 99%
“…For happiness and surprise, changes were much smaller, and for disgust there was a trend for age-related improvements. Modalities other than facial expressions are less studied, but there is evidence for age-related decrements in emotion recognition in lexical stimuli (Isaacowitz et al, 2007), body postures (Ruffman, Halberstadt, & Murray, 2009), visual scenes (St. Jacques, Dolcos, & Cabeza, 2008), and in dynamic auditory cues, namely speech prosody (e.g., Lambrecht et al, 2012;Mitchell, 2007;Mitchell, Kingston, & Bouças, 2011) and nonverbal vocalizations (Lima, Alves, Scott, & Castro, 2013). Although typically young adults are compared with individuals aged 60 and over (''extreme age group'' design; Isaacowitz & Stanley, 2011), a few studies using finer gradations in age revealed that decrements may proceed linearly with advancing age, with significant differences already in middle-age (e.g., Isaacowitz et al, 2007;Lambrecht et al, 2012;Mill, Allik, Realo, & Valk, 2009;Paulmann, Pell, & Kotz, 2008).…”
Section: Aging and Emotion Recognitionmentioning
confidence: 99%
“…Specifically, semantic information compensates for the distorted lexical tone contours in quiet, while natural F 0 contours are important for the recognition of Mandarin sentences in adverse listening conditions. It has been shown that there is an age-related decline in the ability to use F 0 information to separate target message from maskers and to interpret emotional valence of speech (Mitchell et al, 2011;Lee, 2013). A recent study revealed that Mandarin-speaking older listeners scored significantly lower than young listeners in tone recognition (Yang et al, 2015), which might be attributed to reduced neural representation of F 0 information in speech for the older listeners (Anderson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%